Kebijakan Penguatan Pesantren Dengan Program Mu’adalah - Zainal Panani; Mujamil Qomar; Abd. Aziz (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The purpose of writing this article is to find out the policy for strengthening Islamic boarding schools with the mu'ilah program. This research uses a type of library research. Library research is research carried out by reviewing various journals and related reference books. The results of his research show that the implementation of Mu'ilah is an effort to advance and equalize Islamic boarding school education and can also be used to improve the quality of Islamic boarding schools. The Mu'ilah (equalization) curriculum is applied to Salaf or modern Islamic boarding schools with certain criteria and requirements. The curriculum of salaf Islamic boarding schools that obtain Mu'ilah or equalization is the yellow book curriculum plus the general education curriculum which includes the general education curriculum as referred to in paragraph (1) (article 10 paragraph 3 PMA no. 18 of 2014) containing at least: a) education citizenship (al-tarbiyah al-wathaniyah); b) Indonesian (al-lughah al-indunisiyah); c) mathematics (al-ri.yadhiyat); and d) Natural sciences (al-ulum al-thabi'iyah). The mu'ada curriculum regulations are contained in the Islamic Boarding School Law no. 18 of 2019 concerning Islamic Boarding Schools. The Mudalam education curriculum standards listed in PMA Number 31 of 2020 concerning Islamic boarding school education CHAPTER III Mudalam Education include: curriculum, educators and education staff, assessment and graduation, facilities and infrastructure. If it is related to the National Education Standards listed in the Government Regulation of the Republic of Indonesia Number 57 of 2021 Article 3 concerning National Education Standards, namely with 8 standards, then Islamic boarding schools only apply 5 standards, namely: (1) Content Standards; (2) Process Standards; (3) Standards for Educators and Education Personnel; (4) Graduate Competency Standards; and (5) Facilities and Infrastructure Standards.